A double-blind, 377-subject randomized study identifies Ruminococcus, Coprococcus, Christensenella, and Collinsella as long-term potential key players in the modulation of the gut microbiome of lactose intolerant individuals by galacto-oligosaccharides. (1st January 2021) - Azcarate-Peril, M. A.; Roach, J.; Marsh, A.; Chey, William D.; Sandborn, William J.; Ritter, Andrew J.; Savaiano, Dennis A.; Klaenhammer, T. R.
ABSTRACT: Background . Our recent publication (Chey et al., Nutrients 2020) showed that a 30-day administration of pure galacto-oligosaccharides (GOS) significantly reduced symptoms and altered the fecal microbiome in patients with lactose intolerance (LI). Results . In this addendum, we performed an in-depth analysis of the fecal microbiome of the 377 LI patients randomized to one of two GOS doses (Low, 10–15 grams/day or High, 15–20 grams/day), or placebo in a multi-center, double-blinded, placebo-controlled trial. Sequencing of 16S rRNA amplicons was done on GOS or placebo groups at weeks zero (baseline), four (end of treatment), nine, 16 and 22. Taxa impacted by treatment and subsequent dairy consumption included lactose-fermenting species of Bifidobacterium, Lactobacillus, Lactococcus, and Streptococcus . Increased secondary fermentation microorganisms included Coprococcus and Ruminococcus species, Blautia producta, and Methanobrevibacterium . Finally, tertiary fermenters that use acetate to generate butyrate were also increased, including Faecalibacterium prausnitzii, Roseburia faecis, and C. eutactus . Conclusions . Results confirmed and expanded data on GOS microbiome modulation in LI individuals. Microbiome analysis at 16 and 22 weeks after treatment further suggested relatively long-term benefits when individuals continued consumption of dairy products.